A New 7‐Azaindole Structure Analog: Molecular Docking, Synthesis and Preliminary Biological Activity in Vitro for Anticancer. Issue 10 (27th September 2022) - Zhan, Yifeng; Tong, Hang; He, Shibo; Zhu, Hongda; Guo, Huiling; Sun, Hongmei; Liu, Mingxing
Abstract: In this work, a series of 7‐azaindole analogs were designed by the bioisosteric principle based on the pharmacodynamic parent nucleus. Moreover, 5‐[(5‐chloro‐1 H ‐pyrrolo[2, 3‐ b ]pyridin‐3‐yl)methyl]‐ N ‐[6‐(trifluoromethyl)pyridin‐3‐yl]methylpyrimidin‐2‐amine (compound P1 ) with the strongest interaction with colony‐stimulating factor 1 receptor (CSF‐1R) was screened by molecular docking. Compound P1 was successfully prepared by the six‐step reaction with HPLC purity of 99.26 % and characterized by 1 H‐NMR and ESI‐MS spectra. In vitro bioactivity study showed that compound P1 appeared the cytotoxicity to MCF‐7 and A549 cells, especially to HOS cells (IC50 =88.79±8.07 nM), while it had lower toxicity to normal L929 cells (IC50 =140.49±8.03 μM). In addition, compound P1 could induce HOS cell death by apoptosis and blocking the G0/G1 phase at nanomolar concentrations. The obtained results indicated that compound P1 might be a promising candidate compound for anticancer drug. Abstract :